Visualizing collaborative conservation: a picture is really worth a thousand words! - Bentrup, Gary, author (Colorado State University. Libraries, 2009)
One of the main challenges facing collaborative conservation efforts is the need to clearly communicate land management alternatives with diverse stakeholders and to engage all participants in shaping these alternatives into a mutually agreeable plan of action. Despite the use of GIS maps, management plans, and engineering drawings, many stakeholders still have difficulty in conceptualizing what a proposed conservation action will actually look like on the landscape. This lack of understanding often creates impassable barriers in the collaborative planning process and is exacerbated by the long-term commitment that many conservation actions require from stakeholders. Stakeholders often lament if they could only see a picture of the proposed action to aid in their decision making. Collaborative initiatives now have a tool to translate these plans into real-life pictures or images called visual simulations. Visual simulations are digital images which have been altered to illustrate conservation alternatives. Using image-editing software and a digital image of the project area, photo-realistic conservation alternatives can be "created" through the addition or removal of vegetation and other landscape objects. In a relatively short time, conservation alternatives addressing invasive species, forest health, riparian restoration, and other issues can be illustrated at various stages of development, compositions, and arrangements on the landscape. The USDA National Agroforestry Center has developed the CanVis Visual Simulation Kit consisting of CanVis, an image-editing software program designed specifically for conservation applications, and the Visual Simulation Guide, a multi-media reference manual on how to create simulations for natural resource planning. This free tool enables resource professionals to readily show how science is translated into management practices and alternatives on the ground and helps reduce any socio-economic or language barriers, a particularly valuable attribute in today's diverse and sometimes contentious planning environment. Visual simulations promote sustainability by communicating ideas clearly, by inviting feedback on the alternatives, and by instilling a sense of shared ownership in the conservation system so that it is supported and maintained for long run.
Presented at the Bridging the gap: collaborative conservation from the ground up conference, September 8-11, 2009, Colorado State University, Fort Collins, Colorado, sponsored by the Center for Collaborative Conservation, https://collaborativeconservation.org/. This conference brought together people with experience working collaboratively to achieve both conservation and livelihood goals in tribal nations, rangelands, forests, watersheds, agricultural lands, and urban areas. The presenter is affiliated with USDA National Agroforestry Center, U.S. Forest Service.
Keywords: collaborative conservation; visual simulations; CanVis Visual Simulation Kit